2017
DOI: 10.1111/1754-9485.12617
|View full text |Cite
|
Sign up to set email alerts
|

Dose discrepancy between planning system estimation and measurement in spine stereotactic body radiation therapy: A case report

Abstract: Stereotactic body radiation therapy (SBRT) to treat spinal metastases has shown excellent clinical outcomes for local control. High dose gradients wrapping around spinal cord make this treatment technically challenging. In this work, we present a spine SBRT case where a dosimetric error was identified during pre-treatment dosimetric quality assurance (QA). A patient with metastasis in T7 vertebral body consented to undergo SBRT. A dual arc volumetric modulated arc therapy plan was generated on the Pinnacle tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…6(d)] in agreement with the literature 10. It was shown previously that 90 control point plans were the most complex, and while this had no impact on the plan coverage/conformity, it did have an impact on accuracy/deliverability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6(d)] in agreement with the literature 10. It was shown previously that 90 control point plans were the most complex, and while this had no impact on the plan coverage/conformity, it did have an impact on accuracy/deliverability.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study found accuracy improvements for an individual SBRT spine case when the gantry spacing between control points was decreased from 4° to 3° 10. The delivery accuracy of different IMRT and VMAT techniques has also been investigated for spinal treatment 11.…”
Section: Introductionmentioning
confidence: 99%